A CASE STUDY OF STRATEGIC PARTNERSHIP PT. ERANDRA SURYA MANUNGGAL WITH SMALL POTENTIAL CMT - Yustinus, Erick; Heriyati, Pantri (Bina Nusantara University, 2011)
PT. Erandra Surya Manunggal (PT. ESM) manufactures children's clothing, ranging from 0-1 year old infants to children aged 2-14 years. Clothing market in Indonesia is strongly influenced by holidays and festivals, to accommodate the demand of the market PT. ESM selected several small potential CMTs for cooperative agreement to provide the necessary machines in the production process. PT.ESM made a strategic partnership with small potential CMTs to secure the supply of the products. In this case study, indepth interviews will be conducted in order to have the insight and achieve the comprehensiveness of the problem and the issue related with the case. Interveiews were mostly conducted with Mr. Indra as the CEO of PT. ESM to explore the business process, issues, included how the CEO took the decisions, the risks involved in partnership with the CMTs. This case study is also attempt to discuss the strategy, formulation, determination of the CMTs and the evaluation of partnership with CMTs. It also provides insight on the production process and how the interconnection and how the partnership between PT ESM and CMTs. There are some forms of research design. The field research, library research and based on knowledge and imagination of the author describe the condition and environment.